2017
DOI: 10.1093/europace/eux111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epicardial vs. endocardial reimplantation in pacemaker-dependent patients with device infection

Abstract: We observed similar in-hospital outcomes in our EPI and TP cohorts. Twenty-five percent of the patients initially paced by a TP strategy finally needed an epicardial device, mainly because of infection of their TP lead. Use of TP resulted in lower rates of late endocarditis and device reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…As the coronary sinus and target vein were occluded, all our patients underwent epicardial lead implantation through a small transthoracic incision. Huntley et al and Perrin et al reported that the outcomes of reasonable epicardial lead implantation are similar to those of endocardial lead implantation [Huntley 2018;Perrin 2018].…”
Section: Discussionmentioning
confidence: 90%
“…As the coronary sinus and target vein were occluded, all our patients underwent epicardial lead implantation through a small transthoracic incision. Huntley et al and Perrin et al reported that the outcomes of reasonable epicardial lead implantation are similar to those of endocardial lead implantation [Huntley 2018;Perrin 2018].…”
Section: Discussionmentioning
confidence: 90%
“…Management options for pacemaker-related infections include epicardial lead reimplantation before device extraction or temporary pacing with delayed endocardial reimplantation. Perrin et al reported the latter option had a reduced risk of late endocarditis, though there was no difference in long-term mortality between the two strategies [ 7 ]. Amarousi et al reported both strategies offered an excellent success rate and low risk of complications with lower hospital length of stays for surgical epicardial lead placement [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amraoui et al in a retrospective analysis of 80 consecutive pacemaker‐dependent patients bridged with externalized pacing lead for 4‐14 days reported excellent short‐ and long‐term effects with no early lead dislodgement and no infection recurrence at 1 year follow‐up . Of note, Perrin et al presented follow‐up outcomes in the group of 52 pacemaker‐dependent patients who were bridged with screwed‐in temporary lead for 11.1 ± 9.7 days and retrospectively followed up for a mean period of 25.2 months: Eight patients (15.4%) developed vegetations on their temporary lead; one temporary lead dislodged with sudden loss of capture; and one patient developed a CIED reinfection after 21 months of follow‐up . Undoubtedly, a prospective study would be required to fully assess the long‐term safety of temporary lead bridging.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, a prospective study would be required to fully assess the long-term safety of temporary lead bridging. Importantly, in the above-mentioned studies by Macia z g et al and Perrin et al, up to 20% of patients had an infected ICD system, 7,9 whereas in the study by Amraoui et al, ICD patients were excluded from analysis. 8 The technique described above provides an important option for prolonged ICD backup.…”
Section: Discussionmentioning
confidence: 99%